MODELANALISIS GEO-SPASIAL PENENTUAN JALUR TRANSPORTASI INDUSTRI CRUDE PALM OILMENGGUNAKAN ALGORITMA DJIKSTRA - Gunarta, I Ketut; Eriyatno, Eriyatno; Mitfah, Anas (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
Product transportationforcrude palm oil is a complex problem. The complexity is caused by the spread of the location of the oil palm plantationsand mills, the current and potential transportation network, the capacity constraint of each oil factory, the perishable characteristics of the product, the limited of port and port capacity which also depends on their geographical location and the supply fluctuation from plantationsto the factories due to their age.This paper will give an alternative solution which has not yet discussed in the earlier publications by providing a decision alternative related to product transportation from oil mills to ports using GIS based network analyst. The solution is a decision support system that integrate GIS and shortest path model. Spatial decision support system which has built have the capability to accomodate transportation network condition to find the best path from oil mills to the portswhich can be used for further decision making.This research shows that the short distance is not always as the fastest path and the lowest cost due to the condition of the network. The selection of development strategy in CPO agroindustry and the improvement of transportation infrastructures will be able to improve the performance of CPO industry significantly.